METHOD FOR FMD VIRUS 146S COMPONENT CONCENTRATION DETERMINATION WITH REAL-TIME REVERSE TRANSCRIPTION – POLYMERASE CHAIN REACTION IN VACCINE RAW MATERIALS - M. I. Doronin; A. M. Timina; D. A. Lozovoy; V. A. Starikov; D. V. Mikhalishin; N. N. Medvedeva; A. V. Borisov (Ветеринария сегодня)
Method for determination of foot-and-mouth disease (FMD) virus 146S component concentration with real-time reverse transcription – polymerase chain reaction (rtRT-PCR) in vaccine raw materials is developed. Negative regression model of  С146S = (30.269 – Ct )/4.155 type allowing determination of FMDV 146S particle concentrations based on the amplification threshold cycle values (Ct ) is proposed. It has been experimentally proven that the quantity of the 146S component determined by the real-time RT-PCR method using developed regression model and contained in the inoculation dose of FMD vaccine confers protection to the vaccinated animals against generalized FMD of A, O, Asia-1 types. rtRT-PCR method is highly sensitive and allows rapid and highly reliable estimation of the 146S antigen concentration in FMD vaccine. The method for 146S particle quantity determination by real-time RT-PCR using the regression model is reliable and demonstrates high correlation (95.5–99.0%) with the complement fixation test results.